Characterization of an Environmental Multidrug-Resistant Acinetobacter seifertii and Comparative Genomic Analysis Reveals Co-occurrence of Antimicrobial Resistance and Metal Tolerance Determinants - Furlan, João Pedro Rueda; de Almeida, Otávio Guilherme Gonçalves; De Martinis, Elaine Cristina Pereira; Stehling, Eliana Guedes (Frontiers in Microbiology, 2019)
Acinetobacter calcoaceticus-Acinetobacter baumannii complex is considered one of the main causes of hospital-acquired infections. Acinetobacter seifertii was recently characterized within this complex and it has been described as an emergent pathogen associated with bacteremia. The emergence of multidrug-resistant (MDR) bacteria, including Acinetobacter sp., is considered a global public health threat and an environmental problem because MDR bacteria have been spreading from several sources. Therefore, this study aimed to characterize an environmental MDR A. seifertii isolate (SAb133) using whole genome sequencing and a comparative genomic analysis was performed with A. seifertii strains recovered from various sources. The SAb133 isolate was obtained from soil of a corn crop field and presented high MICs for antimicrobials and metals. The comparative genomic analyses revealed ANI values higher than 95% of relatedness with other A. seifertii strains than A. calcoaceticus-A. baumannii complex. Resistome and virulome analyses were also performed and showed different antimicrobial resistance determinants and metal tolerance genes as well as virulence genes related to Acinetobacter baumannii known virulence genes. In addition, genomic islands, IS elements, plasmids and prophage-related sequences were detected. Comparative genomic analysis showed that MDR A. seifertii SAb133 had a high amount of determinants related to antimicrobial resistance and tolerance to metals, besides the presence of virulence genes. To the best of our knowledge, this is the first report of a whole genome sequence of a MDR A. seifertii isolated from soil. Therefore, this study contributed to a better understanding of the genetic relationship among the few known A. seifertii strains worldwide distributed.